1994
DOI: 10.1177/0310057x9402200618
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Oxygen Saturation in the 72 Hours after Hip Surgery: The Effect of Oxygen Therapy

Abstract: The aim of this study was to investigate changes in oxygen saturation (SpO2) occurring during the three days following hip surgery in patients in this hospital and to determine to what extent SpO2 might be improved by oxygen therapy for 24 or 72 hours. Eighty-three patients (aged 43-96 years) scheduled for elective total hip replacement or emergency surgery for hip fractures were studied. Forty-four patients had 24 hour postoperative oxygen prescribed by their anaesthetist or surgeon; we randomized these to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Standardized post‐operative management protocols were instituted to streamline patient recovery and rehabilitation . All patients at this institution receive post‐operative oxygen supplementation, in line with evidence supporting the routine use of oxygen therapy for the first 72 h after surgery . Routine mechanical and biochemical venous thromboprophylaxis, as well as preventative pressure sore dressings and antibiotic prophylaxis, are also utilized …”
Section: Discussionmentioning
confidence: 96%
“…Standardized post‐operative management protocols were instituted to streamline patient recovery and rehabilitation . All patients at this institution receive post‐operative oxygen supplementation, in line with evidence supporting the routine use of oxygen therapy for the first 72 h after surgery . Routine mechanical and biochemical venous thromboprophylaxis, as well as preventative pressure sore dressings and antibiotic prophylaxis, are also utilized …”
Section: Discussionmentioning
confidence: 96%
“…Previous trials in patients undergoing hip surgery have focused mainly on preventing hypoxia, and the studies we found examining post-operative oxygen administration, had no classification of hyperoxia. 28,29 . The effect of excessive oxygen administration compared to adequate oxygen administration in this group of patients seems to be inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…However, no clear statement is made about whether pulse oximetry should be continuous or intermittent. The rationale for this statement is based on the findings of Fugere et al 20 who reported that patients who did not receive supplemental oxygen following surgical repair of hip fracture had a greater incidence of desaturation in the first 48 h (oxygen saturation falling below 90%) than patients who did receive supplemental oxygen. Although no attempt was made to infer the causes for this phenomenon, this study did note that normal practice was to keep patients in the supine position for the first 48 h postoperatively.…”
Section: Applicability Of the Evidence To A Clinical Guideline For Edmentioning
confidence: 99%